E-037 What Stroke Patients Post Online About: An Instagram and Twitter Analysis. (23rd July 2022) - Gajjar, A; Jain, A; Dinh Le, A; Salem, M; Hasan, S; Jankowitz, B; Burkhardt, J
Abstract : Introduction: Increased social media usage has allowed many individuals and patients to connect and influence their patient population through providing their own opinions and health experiences. Conducting patient feedback surveys serves as a valuable means for obtaining important information about patients' sense of satisfaction regarding their outcomes, and perioperative needs. In this study, to better understand the patient experience after stroke, the authors sought to assess patient-managed, provider-independent Twitter and Instagram posts on social media to further understand the patient perception of stroke. Methods: A variety of terms ('stroke', 'stroke survivor', 'stroke rehab', 'stroke recovery') were used to search for potentially relevant hashtags to find possible qualified posts on Twitter and Instagram. Four hundred sixty-eight public Instagram posts marked under '#stroke' and '@stroke' including direct references to the patient's own experience were analyzed (June 2018 to July 2021). Twitter posts containing '#stroke' and '@stroke' were identified, and the search results yielded 2, 506 tweets related to the patient's own experience (June 2021 to September 2021). The first or recurrent stroke was identified whenever possible. The posts and tweets were analyzed and coded according to the following criteria of the patient's gender, preoperative or postoperative time of posting as described in the post, and the patient's experience of a stroke. Results: The most common theme on Twitter was raising awareness about stroke (23.4%) and was spreading positivity on Instagram (66.7%). Other common themes on Twitter were recounting symptoms (15.7%), offering, and reaching out for online support (9.6%), and providing a scientific explanation of strokes (7.8%). Other prevalent themes on Instagram included recounting symptoms (42.3%), raising awareness (40.4%), and describing the quality of life (44.0%). 2, 792 of (93.9%) Twitter posts were from patients experiencing their first stroke, and 180 (6.1%) posts were about recurrent strokes. The majority of posts on Instagram (75.7%) and Twitter (77.3%) were made by women. No statistically significant change in theme frequency was found between first and recurrent stroke. Patients who were posting about a recurrent stroke tended to mention positivity less frequently than those positing about their first stroke (p = 0.054). Conclusion: Social media has provided a platform for analyzing unilateral feedback from patients, concurrently as they share their personal experiences and connect with others. Raising awareness and describing their quality of life were the most common themes online. Such platforms help assess patients' satisfaction and guide physicians for better counseling aiming to improve the quality of provided care. Disclosures: A. Gajjar: None. A. Jain: None. A. Dinh Le: None. M. Salem: None. S. Hasan: None. B. Jankowitz: None. J. Burkhardt: None.